Analysis of Promotion Strategy in Increasing Sales at PT Cipta Giri Sentosa - Hilda Ayu Hendrawati; Sukaris Sukaris (Universitas Muhammadiyah Gresik, 2023)
This research aims to analyze appropriate promotional tactics to increase sales at PT Cipta Giri Sentosa. This research is descriptive research with qualitative methods. The analysis technique used is SWOT Analysis. The subjects of this research are marketing managers who take care of the promotion department and several workers who play a role in promotional activities. Primary data collection used interview and observation techniques, while secondary data was obtained from documentation studies. what will happen is that research shows that management skills that can be applied to increase sales are Quadrant 1, the quadrant is in a profitable situation for the company because it carries out promotions using various events or exhibitions that can be participated in, partnership opportunities using pharmacy networks, advertising through social media. opportunities and the power of media, as a result PT Cipta Giri Sentosa can take advantage of existing opportunities and maximize its strengths. The strategy that must be implemented in this condition is to support aggressive growth policies (Growth Oriented Strategy). Proactive growth tactics can start by providing the best service to meet customer needs.